PERTIMBANGAN HAKIM DALAM PENJATUHAN PUTUSAN BEBAS PADA TINDAK PIDANA NARKOTIKA - Arni Lase (LPPM Universitas Nias Raya, 2025)
Narcotics crimes are offenses involving the use of substances or drugs that can cause dependence, whether derived from plants or non-plants. An acquittal can occur if the defendant is truly not proven guilty according to legal facts as charged by the public prosecutor. Decision Number 459 K/Pid.Sus/2017 is one of the decisions where the defendant was acquitted by the judge. Therefore, this research aims to determine and analyze the judge's considerations in handing down acquittal decisions for narcotics crimes. This research uses a type of normative legal research with a statutory regulation approach, case approach, analytical approach by collecting secondary data consisting of primary legal material, secondary legal material and tertiary legal material. Based on the research findings and discussion, it can be concluded that the consideration of the panel of judges in handing down decision number 459 K/Pid.Sus/2017 is in accordance with Article 183 of the Criminal Procedure Code and the charges brought by the public prosecutor, namely Article 112 of Law Number 35 of 2009 concerning Narcotics that Legal facts have been found revealed in the trial which state that the defendant is not guilty. However, on the other hand, the author also believes that the judge did not really investigate the origins of the narcotics presented by the public prosecutor at the trial, which would be especially true if, as is known, the defendant was not proven to possess the narcotics. The author suggests that so that the Panel of Judges does not hand down an acquittal, the public prosecutor must be more careful, detailed, comprehensive and careful in preparing the indictment and demands.